Interventions to Increase Hope in Adult Patients with Cancer: Scoping Review - Erna Rochmawati; Desty Wehelmina Alfons Alfons (STIKep PPNI Jawa Barat, 2021)
Background: Cancer can cause sufferers to lose hope. Interventions to increase hope in cancer patients require interaction and system support so that they can provide enthusiasm and acceptance of the disease. Purpose: This review aims to identify interventions that can raise expectations in adult cancer patients. Method: Review this uses the method scoping reviews according to Arskey and O'Malley, namely: (1) Identification of research questions, (2) identifying relevant research, (3) study selection, (4) mapping data, (5) compiling, summarizing and reporting results. The search was carried out at PubMed, CINAHL, Psyc Info. Inclusion Criteria: English language articles, published in the last 10 years, do not limit the place or location. Exclusion Criteria: Articles discussing pediatric patients with cancer, adolescent patients with cancer, qualitative research methods. Search strategy using keywords with Medical Subject Heading / MeSH: cancer, oncology, hope, psychotherapy or counseling, intervention or effectiveness. Result: There are five articles reviewed in this scoping review. The research was conducted: China (n = 1), Canada (n = 1), Iran (n = 3). Interventions that can increase hope in adult cancer patients: Workshop, interventions group logo therapy, interventions supportive- expressive discussion groups, we chat-based life review programs (WBLRP), interventions spiritual group therapy. Cancer is being able to think in a positive direction, being grateful, being motivated, having self-confidence and increasing Hope. An intervention that is easy to apply is the Workshop Intervention, because participants are only asked to draw and paste from easily available materials such as used paper, used cloth and after being arranged into a shape, participants are asked to tell about the results that have been made. Conclusion: Hope is an important aspect in the patient's disease trajectory, especially in relation to the healing process. This study will enable nurses to gain an in-depth understanding of interventions to increase expectations so as to maintain and increase patient expectations.